Locally Advanced Pancreatic Adenocarcinoma: Where Are We and Where Are We Going? - Chang, Bryan W; Saif, Muhammad W (JOP. Journal of the Pancreas, 2011)
Eight abstracts highlighting the continued evolution of the management of locally advanced pancreatic cancer were presented at the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium (Abstracts #195, #239, #259, #281, #287, #305, #307, #324). These studies address key issues including the role of novel targeted therapies, what chemotherapy regimen should be used in conjunction with radiotherapy, and whether locally advanced pancreatic cancer can be managed with chemotherapy alone. Image: Yale University. New Haven, CT, USA. (logo)